PENGAMPUNAN PAJAK DALAM PERSPEKTIF KEADILAN - S. Endang Prasetyawati (KEADILAN PROGRESIF, 2019)
Tax amnesty will be able to increase investment as expected by the government in an effortto increase economic growth, moreover at this time the tax ratio shows a low number asproof that there are still many taxpayers who do not / have not implemented their rights andobligations in accordance with legislation -invitation. Tax amnesty in the form of tax debtexemption along with sanctions raises legal issues, how is the concept of tax amnesty inrelation to justice as an effort to develop tax law. This research was conducted with anormative juridical approach. Therefore the main data used is secondary data in the form oflaws and regulations. Data analysis was carried out qualitatively. Based on the results of thestudy, vertical and horizontal justice in tax imposition is not sufficient when applied in taxamnesty. In tax amnesty that is more highlighted is justice which brings benefits to societyand the state. The suggestion of using the tax amnesty model in the form of exemption fromthe obligation to pay tax debt that was previously not paid and the exemption from impositionof sanctions must be followed by strict law enforcement after forgiveness by prioritizingadministrative legal instruments.